TINJAUAN KEBIJAKAN EKONOMI ISLAM PADA MASA DAULAH UTSMANIYAH: STUDI ATAS KEBIJAKAN FISKAL, SISTEM MONETER, WAKAF, DAN KEPEMILIKAN - Rafly, Muhammad; Haeriyah, Hamzah (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research is in the discourse of Islamic economics, especially the historical study of the economic system implemented in the Ottoman Caliphate. This study aims to identify and analyze the principles of Islamic economics implemented in fiscal, monetary, ownership, and state roles during the Ottoman government. The research method used is qualitative-descriptive with a literature study approach. Data were collected through a review of ten relevant scientific sources, consisting of journal articles, books, and academic studies related to the Ottoman economic system. No hypothesis was proposed, given the exploratory nature of this study. The findings show that the Ottoman Empire implemented a sharia-based economic structure systematically, such as the use of hisbah institutions, waqf systems, ownership divisions, and dinar-dirham-based monetary policies to banknotes. This paper contributes to enriching Islamic economic literature by presenting a historical perspective as a reflection of the application of sharia economics in the governance system. The results of this study are important for broadening the understanding of the Islamic economic model that has been proven to work on a state scale, and can be a reference in the development of contemporary Islamic economics based on institutions.